2012
DOI: 10.4171/lem/58-3-2
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of closed geodesics on the modular surface, and Duke's theorem

Abstract: Abstract. We give an ergodic theoretic proof of a theorem of Duke about equidistribution of closed geodesics on the modular surface. The proof is closely related to the work of Yu. Linnik and B. Skubenko, who in particular proved this equidistribution under an additional congruence assumption on the discriminant. We give a more conceptual treatment using entropy theory, and show how to use positivity of the discriminant as a substitute for Linnik's congruence condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 15 publications
4
83
0
Order By: Relevance
“…The point here being is that for a given center x, outside a countable set or radii μ(∂xB r ) = 0. Lemma 2.9 is a slight adaptation of Lemma 4.5 from [5]. For convenience, we added the full proof in the Appendix (see also Remark A.3).…”
Section: Maximal Entropymentioning
confidence: 99%
“…The point here being is that for a given center x, outside a countable set or radii μ(∂xB r ) = 0. Lemma 2.9 is a slight adaptation of Lemma 4.5 from [5]. For convenience, we added the full proof in the Appendix (see also Remark A.3).…”
Section: Maximal Entropymentioning
confidence: 99%
“…We will show the proposition using [BK83], more precisely in the form of Lemma B.2 in [ELMV12]: There it is shown that for any small δ > 0, the entropy of µ is the limit as λ → 0 of…”
Section: Estimate Of Metric Entropy and Proof Of Theorem Amentioning
confidence: 99%
“…3.42-3.45, you will appreciate the appearance of continued fractions here. Other references for the distribution of geodesics in the fundamental domain of the modular group are: Duke [144] and Einsiedler et al [154].…”
Section: Questionsmentioning
confidence: 99%
“…3, 13, 18, 23, 29, 133, 164, 186-191, 193, 195, 317, 342, 361 heat kernel, 164, 165, 186, 193 25-29, 190, 192, 193, 195 25-29, 121, 142, 188, 190, 191, 193-195 probability 54,63,79,80,150,153,154,163,196,202,207,208,243,248,256,257,267,288 …”
Section: Hintmentioning
confidence: 99%
See 1 more Smart Citation